PENGARUH PENGGUNAAN MEDIA PHOTOVOICE TERHADAP BERPIKIR KREATIF SISWA SEKOLAH DASAR - Kurnia Illahi, Antika Tariski; Supriyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The motivation behind this research comes from students challenges in speaking Indonesian correctly and honestly. May be displayed in the use of poorly chosen words, awkward phrasing, and inadequate formal essay writing. This study used a random sampling method to examine the relationship between the use of photovoice media and the writhing ability of third grade students at SDN Waung. Before and during testing, as well as documentation of activities, assessment of writing skills, complemented by observation as the main source of information or data collection. Data analysis was based on a normality test carried out using the paired sample T-test, because the data supports a normal distribution. The results of the paired sample T-test show the 2-Tailed significance threshold.